Development of Management Information Systems for Supply Chain Optimization - Maimun; Lidiana (STMIK Indonesia Banda Aceh, 2023)
Development of Management Information Systems for Supply Chain Optimization is research that aims to improve supply chain efficiency and performance through the application of information technology. The research method used is system requirements analysis, system design, and implementation of an integrated software-based system. The research results show that the use of management information systems allows better monitoring of all activities in the supply chain, including inventory management, raw material procurement, production, distribution and inventory management. With the adoption of this technology, organizations can optimize the flow of information and identify weak points in the supply chain, thereby improving responsiveness to changes in market demand and reducing operational costs. The conclusion of this research is that the development of management information systems plays an important role in increasing the efficiency and resilience of supply chains in facing dynamic market challenges.